Production and characterisation of a recombinant cold adapted lipase from Pseudomonas sp. LSK25 isolated from Signy Station, Antarctica - Salwoom, Leelatulasi (2019)
Enzyme-mediated catalysis has increasingly become a preferred approach in numerous industries, facilitating reactions with fewer by-products, consuming less energy and adding value to products. Increasing interest has been taken in enzymes obtained from organisms living in extreme environments, for instance from Antarctica, based on their ability to function under harsh conditions. Cold-adapted enzymes, especially lipases, have gained importance in commercial applications. These enzymes are favoured for their high catalytic activity at low temperatures, reducing energy costs and improving the cost-effectiveness of industrial production. Therefore, the search for new cold-adapted lipases is an ongoing effort. Lack of indepth study on the production and characterisation of cold adapted lipases hinder our understanding of the potential of these enzymes. In order to better understand the biocatalytic potential of these unique cold-adapted lipases, in-depth studies of their production, biochemical characterisation and structural analysis are pivotal. The current study set out to identify, isolate, production, express, characterise and predict the structure via in silico simulation, of a new cold-adapted lipase produced by a soil bacterium originally isolated from Signy Island, Antarctica. The strain Pseudomonas sp. LSK25 was isolated and its lipase gene expression was quantified. Lipase production of strain LSK25 was investigated via optimised physical and nutritional factors. A recombinant lipase gene (LSK25 lipase), consisting of 1432 nucleotides encoding 476 amino acids for a protein of predicted molecular mass of 65kDa, was successfully expressed at optimal conditions of 25°C, 0.1 mM IPTG (inducer) and 16 h post-induction time. The enzyme was expressed in the form of an inclusion body and was purified via one step Ni-Sepharose affinity chromatography. Biochemical characterisation of LSK25 lipase showed an optimal and stable temperature profile around 25-30 °C with high lipolytic activity retained at pH 6. Elevated lipolytic activity was also observed in the presence of the Ca²⁺ ion. The enzyme was able to hydrolyse long chain lipid substrates. An added advantage of LSK25 lipase is its ability to tolerate a wide range of organic solvents. The in silico study of the predicted structure of the cold-adapted LSK25 lipase further improved the understanding of the stability and molecular flexibility of this enzyme over a broad range of temperature.